The US-China Trade Competition: An Overview - SIBY K M (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
An impending trade war between US and China, the world’s two largest economies can cause insurmountable consequences of unfathomable magnitude. It can cause distortions in the complex web of interconnected commodity and value chains sprawled across the boundaries, ultimately leading to suboptimal social welfare of the international community. The present paper intends to provide an overview of the US-China trade imbalance and resulting trade tensions that it begets and proposes the likelihood of not getting the scenario escalated.